Rethinking MSMEs Tax Exemptions in Indonesia: Force Majeure and Tax Justice During COVID-19 - Tri Eka Saputra; Askari Razak (Journal of Judicial Review, 2026)
This study aims to reassess tax exemption policies for Micro, Small, and Medium Enterprises (MSMEs) during the COVID-19 crisis in Indonesia within the framework of fiscal justice principles and the doctrine of force majeure. Employing a purely normative legal research method, with statutory and philosophical approaches, this research analyzes the prevailing tax law norms, the potential integration of force majeure into the taxation legal system, and the urgency to reconstruct a more responsive principle of tax justice during national emergencies. The key findings indicate that tax incentive policies for MSMES remain sectoral in nature, rely solely on administrative approaches, and have yet to fully adopt force majeure as a legal foundation for granting fiscal relief. The concept of tax justice grounded in public law principles and legal responsiveness must be advanced to shape a more adaptive and equitable tax system. This study has implications for strengthening the national tax regulatory framework, particularly in developing crisis-responsive policies based on substantive justice, and opens the path for new legislation that clarifies the scope and operationalization of force majeure within the fiscal context.